2020
DOI: 10.1111/are.14896
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities and predicted nitrogen metabolism of heterotrophic‐ and probiotic‐based biofilms used for super‐intensive indoor shrimp culture

Abstract: Biofilm-based aquaculture systems constitute a promising alternative for intensive shrimp rearing. Microorganisms forming biofilms can recycle the nitrogen compounds the production units improving the water quality while using zero or limited water exchange. This study aimed to compare the taxonomic profiles and the predicted functions related to the transformation of nitrogenous compounds between a heterotrophic-(HtB) and a probiotic biofilm (PrB), and the effect of these on the water quality and the producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Previously there are reports of microbial sequences annotated to energy metabolism, xenobiotics biodegradation, membrane transport in intestinal microbiota from two cultured stages (30 d and 60 d) of L. vannamei ( Gao et al, 2019 ), even so, their implications in the intestine shrimp are not yet elucidated. However, regarding energy metabolism, such as nitrogen metabolism, Ortiz-Estrada et al (2021) reported genes encoding enzymes implicated in the nitrogen metabolism in probiotic biofilm from a zero recharge shrimp culture, which registered better water quality parameters than a heterotrophic biofilm. Nitrogenous metabolites, particularly unionized ammonia (NH 3 ) and nitrite (NO 2 ) are toxic for shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…Previously there are reports of microbial sequences annotated to energy metabolism, xenobiotics biodegradation, membrane transport in intestinal microbiota from two cultured stages (30 d and 60 d) of L. vannamei ( Gao et al, 2019 ), even so, their implications in the intestine shrimp are not yet elucidated. However, regarding energy metabolism, such as nitrogen metabolism, Ortiz-Estrada et al (2021) reported genes encoding enzymes implicated in the nitrogen metabolism in probiotic biofilm from a zero recharge shrimp culture, which registered better water quality parameters than a heterotrophic biofilm. Nitrogenous metabolites, particularly unionized ammonia (NH 3 ) and nitrite (NO 2 ) are toxic for shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important since the organic matter in the water can turn into ammonia, a highly toxic compound [ 29 ] that can cause a mortality rate of up to 100% in vannamei shrimp cultures [ 30 ]. Probiotics reduce the ammonia content of water through nitrification and denitrification [ 31 ]. In addition, the dissolved oxygen content in the water increases when probiotics are present since they break down organic matter that can then be used by oxygen producers as nutrients to facilitate photosynthesis [ 32 ].…”
Section: Probiotic Mechanisms To Improve Vannamei Shrimp Aquaculture ...mentioning
confidence: 99%
“…For example, due to their ability to utilize many organic substrates, microorganisms have been used to maintain water quality, particularly by the autotroph nitrifying bacteria. In addition, their role in controlling pathogens in disease management and minimizing environmental impacts in the system has also been widely documented (de Mello Júnior et al, 2021; Martínez‐Córdova et al, 2017; Ortiz‐Estrada et al, 2020).…”
Section: Use Of Microorganisms In Aquaculturementioning
confidence: 99%